Right of Apartment/Condominium Owners on the Land on which the Building is Located in the Context of Conversion of the Right of Use into the Right of Ownership on the Construction Land - Cvetić, Radenka Milorad (Zbornik radova Pravnog fakulteta u Novom Sadu, 2021)
Initially the paper recalls that the apartment/condominium ownership is a complex legal construct, which, as a special form of ownership, is the legal institute of modern age. Thereupon, the reasons underlying its legal recognition and widespread use have been indicated, taking into account its deviations from the general ownership regime. Complexity of the apartment/condominium ownership stems from its specific object. Namely, three components of this legal construct: the right on the separate unite of the building (which could be in the the exclusive ownership, co-ownership or in joint ownership), the right on the joint parts of the building (in joint ownership of apartment owners), and the right on the land on which the building is located (in co-ownership of apartment owners), should be normatively shaped and systematically coordinated. Special attention has been paid to the right on the land, from the viewpoint of its peculiarity during the development of a legal system in Serbia after the World War II. The process of conversion, i.e. transformation of the right of use into the right of ownership in Serbia has begun in 2009 by entering into force of the still applicable Planning and Building Act. Evolution of the regulation of the rights of apartment/condominium owners on the land on which the building was erected (including the land which serves for its regular use), from 2009 to 2020, has been examined in detail in the light of its adequacy and capacity to contribute to the (re)establishing of the legal unity of the immovable property, as well as to the prevention of contentious situations.